Expressing the NOANET GNSS network to the Hellenic Geodetic Reference System of 1987 (HGRS1987): A synergy between Geodesy and Geodynamics - Ampatzidis, Dimitrios; Kalamakis, Nikolaos; Katsambalos, Konstantinos Vasileios (Bulletin of the Geological Society of Greece, 2018)
In the present study we describe an algorithm which allows the expression of the coordinates of the NOANET (National Observatory of Athens CORS Network) to the official Greek geodetic reference system (HGRS87). The algorithm exploits the estimated velocities of twelve NONET stations. The main idea is to transform the coordinates (as well as the velocities) from the International Terrestrial Reference Frame 2008 (ITRF2008) to the HGRS1987. This is realised by (a) the use of the 3D time-dependent transformation model and (b) using the transformation tool provided by the Greek Cadastral and Mapping Agency. The final products are the projection coordinates (X,Y) and the orthometric heights of the twelve stations. We expect accuracy better than 10 cm for the projection coordinates, while for the estimation of the heights, the accuracy remains uncertain.